Cannabidiol in the treatment and prevention of Alzheimer's disease - a comprehensive overview of in vitro and in vivo studies - Paulina Drożak; Urszula Skrobas; Martyna Drożak (Kazimierz Wielki University, 2022)
Introduction and purpose. Dementia is a major public health problem. Alzheimer's disease (AD) accounts for 60% of dementia cases. However, AD is currently considered as an incurable disorder and the only few drugs available for its treatment are mostly symptomatic. In the quest for novel drugs for this devastating disease, cannabidiol (CBD) has been recently gaining attention due to its multiple properties, such as an ability to interact with various receptors, anti-inflammatory and antioxidative effects and many more. The aim of this review article was to summarize findings on the effect of CBD on AD with a focus on molecular mechanisms of CBD's action and therapeutic effects which it exerts. Description of the state of knowledge. In vitro studies, carried out on cell models of AD, showed anti-inflammatory and antioxidative properties of CBD through a suppression of pro-inflammatory genes and causing a reduction of production of, among others, nitric oxide. Moreover, CBD was proven to decrease amyloid β (Aβ) production, reduce formation and aggregation of tau fibrils, protect against microglial and Aβ-induced neurotoxicity and prevented the Aβ-induced deficit in long-term potentiation in hippocampus. In vivo studies, conducted mostly on mice models of AD, indicated that CBD improves memory and spatial learning, reverses deficit in social and object recognition, reduces anxiety-like behaviors and improves glucose metabolism. One study including humans demonstrated that CBD enhances cerebral blood flow in hippocampus. Currently there are two ongoing clinical trials on the use of CBD in AD-associated agitation. Conclusions. Both in vitro and in vivo studies indicate that cannabidiol appears promising in the treatment and prevention of Alzheimer's disease.